2022
DOI: 10.1002/dta.3426
|View full text |Cite
|
Sign up to set email alerts
|

Driving license regranting: Hair EtG, serum CDT, and the role of sociodemographic and medicolegal variables

Abstract: Driving under the influence (DUI) of alcohol is a road safety problem. Driving license regranting is based on the evaluation of medicolegal and toxicological variables that may include serum carbohydrate‐deficient transferrin (CDT) and hair ethyl glucuronide (hEtG).The aim of the study was to compare the diagnostic performance of CDT and hEtG in a population of DUI offenders. Other factors potentially associated with heavy alcohol use were explored. The population included DUI offenders examined during the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…The choice to use the CPT-3 is innovative compared to other studies and allowed the analysis of specific aspects of attention linked to SUD and driving impairment [ 18 , 23 ] in a population of subjects examined for driver's license reinstatement. The integrated methodological approach allowed us to objectively assess the current use of psychoactive substances in this context [ 33 ]. The population studied was unusual compared to other populations reported in the literature because of its peculiar characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The choice to use the CPT-3 is innovative compared to other studies and allowed the analysis of specific aspects of attention linked to SUD and driving impairment [ 18 , 23 ] in a population of subjects examined for driver's license reinstatement. The integrated methodological approach allowed us to objectively assess the current use of psychoactive substances in this context [ 33 ]. The population studied was unusual compared to other populations reported in the literature because of its peculiar characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Aboutara et al compared CDT, EtG, and PEth 16:0/18:1 concentrations in liver transplant patients, the latter being the most sensitive 12 . Cinquetti et al observed poor agreement between EtGH and CDT in driving under the influence offenders 13 . Other research groups found that detection of PEth and EtGH is limited after a one time alcohol ingestion or repetitive drinking of small amounts, respectively 14–16 …”
Section: Introductionmentioning
confidence: 99%
“…12 Cinquetti et al observed poor agreement between EtGH and CDT in driving under the influence offenders. 13 Other research groups found that detection of PEth and EtGH is limited after a one time alcohol ingestion or repetitive drinking of small amounts, respectively. [14][15][16] In addition to the determination of ethanol biomarkers, self-rating questionnaires such as Alcohol Use Disorders Identification Test (AUDIT), AUDIT-Consumption (AUDIT-C), or Cut down-Annoyance-Guilty-Eye opener (CAGE), as well as drinking diaries, are frequently used in clinical settings.…”
mentioning
confidence: 99%
“…3 Furthermore, the SoHT meeting in Verona featured research on the identification and quantification of alcohol abuse biomarkers, their stability, and their correlation with exposure and other biomarkers. 4 Forensic Applications and Interpretation: One of the vital objectives of hair testing is its application in forensic investigations and legal proceedings. The SoHT meeting in Verona emphasized the significance of rigorous interpretation of analytical results and the need for standardized protocols.…”
mentioning
confidence: 99%
“…The impact of hair treatments on the oxidation/decomposition of drugs in hair was also explored, as the long‐term fate of drugs incorporated in the keratin matrix 3 . Furthermore, the SoHT meeting in Verona featured research on the identification and quantification of alcohol abuse biomarkers, their stability, and their correlation with exposure and other biomarkers 4 …”
mentioning
confidence: 99%